A novel HLA class I allele: HLA‐A*24:241. (2nd August 2021) - Zheng, Jie Wei; Xie, Jun Hua; Sun, Ying; Xiang, Dong
Abstract : The HLA‐A*24:241 allele differs from A*24:02:01:01 by one nucleotide substitution at position 319.